2020
DOI: 10.1007/s40618-020-01447-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of parathyroidectomy compared with active surveillance in patients with mild asymptomatic primary hyperparathyroidism: a systematic review and meta-analysis of randomized-controlled studies

Abstract: Objective Parathyroidectomy (PTx) has an established benefit in patients with symptomatic primary hyperparathyroidism (PHPT). However, its efficacy in mild asymptomatic PHPT has not been proven. This study aimed to systematically review and meta-analyze the best available evidence from randomized-controlled trials comparing the efficacy of PTx over conservative management (non-PTx) on skeletal outcomes [fractures and bone mineral density (BMD)], nephrolithiasis risk and quality of life (QoL) in patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Randomized clinical trials in patients with mild pHPT found that PTX improved bone mineral density and reduced serum calcium, but its role in the risk of fracture could not be ascertained owing to the small number of patients included in these trials. 32 Observational studies found that the risk of fracture appeared to be lower after rather than before surgery, 17 but this finding was confounded by the observation that those who underwent PTX had lower risk than those who were treated conservatively. 33 In the time-dependent analysis in the present study, PTX was associated with a decrease in fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized clinical trials in patients with mild pHPT found that PTX improved bone mineral density and reduced serum calcium, but its role in the risk of fracture could not be ascertained owing to the small number of patients included in these trials. 32 Observational studies found that the risk of fracture appeared to be lower after rather than before surgery, 17 but this finding was confounded by the observation that those who underwent PTX had lower risk than those who were treated conservatively. 33 In the time-dependent analysis in the present study, PTX was associated with a decrease in fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…While there are clear indications for surgical intervention (based on labs, bone mineral density, and symptoms) in mild asymptomatic primary hyperparathyroidism, as well as for secondary and tertiary hyperparathyroidism, the literature is unclear on how long these patients may be observed with non-operative management before they experience progression of disease. 33 , 34 , 35 , 36 Due to the forced delays to operative management that the COVID-19 pandemic posed to these patients, the multi-disciplinary care team played an essential role in observing medical changes and selecting necessary patients for surgical management of patients with functional endocrinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Para-thyroidectomy (PTx) is a highly effective treatment for PHPT, especially in symptomatic patients, since it effectively increases bone mineral density (BMD) and hence reduces the risk of fracture and nephrolithiasis [5]. Although PHPT patients are always asymptomatic, PTx may be done on specific situations, including at least one of the following: firstly serum calcium concentrations > 1 mg/dL above the upper limit of normal, T-score ≤ − 2.5 assessed by dual-energy Xray absorptiometry (DXA) or history of vertebral fracture, nephrocalcinosis or nephrolithiasis or creatinine clearance of < 60 mL/min/1.73 m2, urinary calcium excretion > 400 mg/24 h with a biochemical profile suggestive for increased nephrolithiasis risk, and lastly age < 50 years old [6,7].…”
Section: Introductionmentioning
confidence: 99%